“...FOUGHT... FOR THE SUCCESSFUL IMPLEMENTATION OF THE PARTY’S GENERAL LINE IN THE CONDITIONS OF CHECHNYA”: ABDURAKHMAN AVTORKHANOV AND EARLY SOVIET HISTORIOGRAPHY OF RUSSIAN-CAUCASIAN RELATIONS - Manysev, Sergej Borisovic (History, Archeology and Ethnography of the Caucasus, 2025)
This article examines the development of Soviet historiography of the North Caucasus through the biographical lens of historian Abdurakhman Avtorkhanov. The work is based on both published and previously unstudied materials from collections of the State Archives of the Russian Federation and the Central State Archives of the Republic of Dagestan. As a party functionary and one of Chechnya’s earliest professional historians, Avtorkhanov published several works on regional history between 1930 and 1936. His research focused on the Caucasian War, highlander resistance, post-war interactions between the North Caucasus and the Russian Empire, the Russian Revolution, and the Sovietization of Chechnya. His early writings, aimed at a general audience, were steeped in revolutionary-proletarian ideology and aligned with Marxist principles, though they lacked direct references to Marxist-Leninist classics and theoretical depth. After graduating from the Institute of Red Professors in 1937, Avtorkhanov’s later works exhibit a more structured and logical approach, incorporating extensive archival sources and references to Marxist-Leninist texts. By analyzing archival documents, this study traces the evolution of Avtorkhanov’s historiographical methods and his perspectives on Russian-Caucasian relations, correlating these shifts with his educational and professional development.